Comparing the antimicrobial effectiveness of NaCl and KCl with a view to salt/sodium replacement. - Bidlas, Eva; Lambert, Ronald J. W. (Elsevier, 2008)
A study using a small range of pathogenic bacterial species (Aeromonas hydrophila, Enterobacter sakazakii, Shigella flexneri, Yersinia enterocolitica and 3 strains of Staphylococcus aureus) has shown that potassium chloride has an equivalent antimicrobial effect on these organisms when calculated on a molar basis. Combined NaCl and KCl experiments were carried out and data was analysed using a modification to the Lambert and Lambert [Lambert, R.J.W., and Lambert, R., 2003. A model for the efficacy of combined inhibitors. Journal of Applied Microbiology 95, 734–743.] model for combined inhibitors and showed that in combination KCl is a direct 1:1 molar replacement for the antimicrobial effect of common salt. If this is a general finding then, where salt is used to help preserve a product, partial or complete replacement by KCl is possible.
Keywords: Predictive modelling; Hurdles; Salt; Potassium chloride; NaCl; KCl